'We had to take a hammer to get some roots out' - experiences, motivations and challenges among volunteer dentists: a qualitative study - Gamarra, Saulo; Bärnighausen, Kate; Wachinger, Jonas; McMahon-Rössle, Shannon A. (British dental journal, 2021)
Objectives To address a gap in the literature by examining the experiences, motivations and challenges among volunteer dentists engaged in short-term missions to low- and middle-income countries.
Gesehen am 29.11.2021